ANALISIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS IV SD SWASTA MUHMMADIYAH PANCUR BATU - RD DWI PUSPITASARI RD DWI PUSPITASARI; Sujarwo (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2021)
The background of this research is the low learning achievement of students in science learning due to the factors of learning difficulties experienced by fourth grade elementary school students, especially students' psychological factors. Learning difficulties experienced by students resulted in low achievement in science subjects. The research was conducted to determine the factors that cause learning difficulties experienced by fourth grade elementary school students. This research is a descriptive qualitative research. The subjects in this study were the fourth grade elementary school students, totaling 26 students and those who had learning difficulties, namely students who had KKM scores that did not meet the 18 students. Data collection in this study was done by interview, observation and documentation. Based on the results of the research and discussion that has been described about students' learning difficulties in science subjects in grade IV SD Private Muhammadiyah Pancur Batu, it shows that from the results of interviews and observations of students there are still many who are not interested in learning science because students have difficulty understanding concepts, difficulties in language and not accompanied by supportive media, low student concentration, poor study habits, low intelligence and lack of motivation given by parents. Keywords: : learning difficulties, science learning